KAMUS PENYAKIT DAN TANAMAN OBAT MENGGUNAKAN ALGORITMA SEQUENTIAL SEARCH WITH SENTINEL BERBASIS ANDROID - Dewi Dessy Suprapti; Isnawaty Isnawaty; Jumadil Nangi (semanTIK, 2018)
Various kinds of plants are all around us, and most of these plants can be used as medicinal plants. Most people would know that there are many plants that have benefits and efficacy as a healer of diseases. But, there are many people who don’t know how to make those plants so that they can be functioned as a medicinewhich can cure diseases. Traditional medicine whichmade of plants also can cure a variety of diseases, wether the mild diseases or even a disease that has entered the stages of malignancy.In this study, the searchin gsystem was performed using Sequential Search with Sentinel algorithm on 50 testing data. The keywords that used in the searching process to be compared one by one with the existing data in the database. If the data that searched is located in the original index (L [1..N]), then it means that the data exist (found). However, if the data searched is in the sentinel index (L [n + 1]), then it means the data does not exist (not found).The results of this study shows that the Sequential Search with Sentinel algorithm can be implemented in a dictionary of diseases and medicinal plants application. The system can serve a good result that match the searched data.Keywords—Sequential Search with Sentinel, Searching system, Dictionary of Medicinal Plants